Pembelajaran Tahfidz Alquran pada Anak Usia Dini - Maskur, Abu (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2018)
This study aims to determine the learning of tahfidz alquran in kindergarten (Roudlotul Qurro) Cirebon. The method used in this research is a qualitative method with case study and observation techniques. The results obtained in this study that learning tahfidz the Koran includes three main activities, namely planning, implementation and assessment. Learning planning is carried out before the school year begins through teacher consultation with the school principal. The learning process includes an initial activity (introduction) which begins with greetings, prayers and repetition of memorization that has been memorized beforehand. Then the core activity, namely the delivery of tahfidz alquran material by the way the teacher reads and students follow and then repeat. And finally the closing activity which was closed with a small evaluation and delivery of material to be studied at the next meeting. The assessment is divided into two categories, namely daily assessment and semester assessment. The assessment method used in learning the Koran tahfidz with the method of Tasmi and Musabaqah.